2020
DOI: 10.1177/0300891620914173
|View full text |Cite
|
Sign up to set email alerts
|

Expression of L1CAM and KI-67 in Endometrial Cancer of Egyptian Females: Clinical Impact and Survival

Abstract: Introduction: Endometrial adenocarcinoma is characterized by a good prognosis. However, the disease response shows a significant heterogeneity. Treatment of endometrial cancer (EC) is still based on clinico-pathological parameters, which have limited role in risk stratification. There is a need for more determinant markers, such as L1 Cell Adhesion Molecule (L1CAM), to identify patients at higher risk of relapse and tailor a more convenient treatment. L1CAM has a capacity to enhance cell motility and promote t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Analysis of immunohistochemical expression of Ki67 in sections of women presented with AUB revealed that there is a relation with the age of patients. Similar observation was found in works of Jiang et al, 2020; Gharib et al, 2020 30,41 . On the contrary, this work concluded that the highest mean of percentage of Ki67 expression was in sections of proliferative endometrium.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Analysis of immunohistochemical expression of Ki67 in sections of women presented with AUB revealed that there is a relation with the age of patients. Similar observation was found in works of Jiang et al, 2020; Gharib et al, 2020 30,41 . On the contrary, this work concluded that the highest mean of percentage of Ki67 expression was in sections of proliferative endometrium.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the cases of carcinoma, this study revealed that 8/20 (40%) of sections exhibited expression of the Ki67 of more than 25%. Similar observation was found by others 23,29,30,41 Mean Ki67 values were higher in cases with proliferative endometrium compared to carcinomas and hyperplasia (P <0.01) and there is a marked variation was noticed between the mean Ki67 values of cases with proliferative endometrium and hyperplasia.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations